Effects of Some Turkish Plant Extracts on Carbonic Anhydrase and Cholinesterase Enzymes - URAS, İbrahim Seyda and KÜRŞAT, Murat and KONUKLUGIL, Belma and ŞENTÜRK, Murat (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Cholinesterase inhibitors are valuable compounds that can be used in many different therapeutic applications, including Alzheimer’s disease. Carbonic anhydrase (CA) inhibitors constitute a pharmacological intervention employed for the management and alleviation of various medical conditions, including glaucoma, idiopathic intracranial hypertension. Turkey has a large and diverse flora, home to thousands of plant species. Hundreds of compounds of medicinal importance have been identified from the many plants in this flora. In this study, the inhibitory properties of seven different plant extracts on CA I and II, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes were investigated. The tested extracts showed AChE inhibitory activity with values ranging from 1.26 to 4.20 μg/mL, BChE inhibitory activity with values ranging from 1.32 to 4.24 μg/mL, CA I inhibitory activity with values ranging from 0.74 to 1.82 μg/mL and CA II inhibitory activity with values ranging from 0.033 to 0.067 μg/mL. The extract of Zosima absinthifolia showed a very active inhibition profile against both AChE and BChE (IC50 1.26 ± 0.01 μg/mL for AChE and 1.32 ± 0.02 μg/mL for BChE). The results indicate that these extracts are potent cholinesterases inhibitors and specifically Zosima absinthifolia extract could be evaluated for further studies.